2014
DOI: 10.3349/ymj.2014.55.5.1354
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B Cells Are Inversely Associated with Disease Activity in Rheumatoid Arthritis

Abstract: PurposeThe function of regulatory B lymphocytes is known to be abnormal in inflammatory diseases. However, a recent study indicates that IL-10+ B cells seem to be expanded in rheumatoid arthritis (RA). Therefore, the state of IL-10+ B cells in the peripheral blood from RA patients and healthy controls were investigated.Materials and MethodsCD19+ cells in peripheral blood mononuclear cells were purified from blood samples of RA patients and age and gender-matched healthy controls, and stimulated with CD40 ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…In particular, the ratio between B cells producing TNF and those expressing IL‐10 is higher in RA than in healthy individuals, suggesting that the B‐cell compartment is abnormally pro‐inflammatory in this disease . This is consistent with the report by several studies of a defect in IL‐10 production by B cells in RA patients compared to healthy subjects . BCDT corrects this defect, and the regenerated B‐cell compartment at 22 months post‐rituximab treatment is in fact less ‘pro‐inflammatory’ than in healthy donors with respect to the balance between TNF and IL‐10 production .…”
Section: Rheumatoid Arthritissupporting
confidence: 89%
“…In particular, the ratio between B cells producing TNF and those expressing IL‐10 is higher in RA than in healthy individuals, suggesting that the B‐cell compartment is abnormally pro‐inflammatory in this disease . This is consistent with the report by several studies of a defect in IL‐10 production by B cells in RA patients compared to healthy subjects . BCDT corrects this defect, and the regenerated B‐cell compartment at 22 months post‐rituximab treatment is in fact less ‘pro‐inflammatory’ than in healthy donors with respect to the balance between TNF and IL‐10 production .…”
Section: Rheumatoid Arthritissupporting
confidence: 89%
“…IL-10 producing B cells acted to suppress T cell inflammatory functions in patients with lupus erythematosus and rheumatoid arthritis, (16, 18, 21). We hypothesized that this is true during progressive canine VL.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of multiple autoimmune diseases, including lupus (15), rheumatoid arthritis (16), and chronic granulomatous disease (17), demonstrated that IL-10-producing B cells were critical for dampening inflammatory disease Induction or presence of functional IL-10 producing regulatory B cells had novel therapeutic capacity in these autoimmune diseases (18). Comparatively little is known about these regulatory B cells specifically alter progression of infectious diseases (1922).…”
Section: Introductionmentioning
confidence: 99%
“…There is no specific surface marker or transcription factor of Bregs, and IL-10 production is considered to be the sole identification trait [17]. During the last decade, human Bregs were studied by many research groups and confirmed to be dysfunctional in many autoimmune diseases, such as systemic lupus erythematosus (SLE), immune thrombocytopenia (ITP) and chronic graft-versus-host disease (cGVHD) [19, 29-32]. In this study, we found that the frequency of circulating IL-10-producing Bregs was significantly lower in DCM patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%